Wegener′s Granulomatosis An unusual Presentation - Criton S (Wolters Kluwer Medknow Publications, 2000)
Wegenâ€s granulomatosis is characterized by necortising granulomatous inflammation and vasculitis affecting predominantly small arteries and veins. In its generalized from there is involvement of upper and lower respiratory tract, kidney and often other organs including skin. It may also present as limited organ involvement. A case of Wegenerâ€s granuolmatosis limited to skin is reported